PERAN KEPEMIMPINAN YANG MELAYANI DAN KARAKTERISTIK PEKERJAAN DALAM MEMPENGARUHI KINERJA KARYAWAN PADA PT NIAGA BUNGA CREATIVE - Qusaeri, Muammar Afif Al; Khasbulloh, M. Wahab; Wiliyanto, Wiliyanto; Khasanah, Muthi’atul (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to analyze the influence of servant leadership and job characteristics on employee performance at PT Niaga Bunga Creative. The research employed a quantitative associative approach, with data collected through questionnaires. The population consisted of 80 permanent employees, all of whom were selected as the sample using a saturated sampling technique. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that both servant leadership and job characteristics have a positive and significant effect on employee performance, both partially and simultaneously. The Adjusted R Square value of 0.605 indicates that 60.5% of the variation in employee performance can be explained by the two independent variables. These findings highlight the importance of a service-oriented leadership style and well-designed job characteristics in enhancing employee productivity within the creative industry sector.